The Policy of Combating Violence Against Women: the EU’s Experience - Karlygash Nugmanova; Elmira Kagazbaeva; Indira Ossimbaeva (Современная Европа)
Violence against women is one of the obstacles to gender equality. This problem is relevant to all countries of the world and causes serious concern due to the human rights violation and threat to women's health. It affects women regardless of their religion, ethnicity, class, income, status, age, educational and cultural background. The purpose of the study is to analyse the European Union's policy on the prevention and control of violence against women and to examine the European Union’s legal and policy framework to regulate this issue. The article reviews the role of the European Union in combating gender-based violence and its capacity to implement necessary changes in the national states gender policies. This article presents the results of research into political and international legal principles to prevent violence against women based on the experience of the European Union. The main instrument of European Union institutions influence on the member states' gender violence policies formation is soft policy, which includes formulating strategies, recommendations, and financing of projects. The authors conclude that despite undeniable progress in gender equality and work in this field, as well as the current EU legal framework which is aimed at combating gender-based violence, the results of the political transformation in this area are not yet sufficient.